DISHARMONISASI PERATURAN BUPATI TANAH DATAR NOMOR 10 TAHUN 2021 TENTANG PEDOMAN TEKNIS PERATURAN DI NAGARI DENGAN PERATURAN DAERAH PROVINSI SUMATERA BARAT NOMOR 7 TAHUN 2018 TENTANG NAGARI - Nesti Rahmadani; Sulastri Caniago; Roni Efendi (Institut Agama Islam Negeri Batusangkar, 2023)
This study examines the disharmonization between Tanah Datar Regent Regulation Number 10 of 2021 concerning technical guidelines for regulations in Nagari and West Sumatra Province Regional Regulation Number 7 of 2018 concerning about Nagari. The problem is the Regent regulation does not pay attention to the procedures, order, and hierarchy of laws and regulations, internal factors violate the principle of laws and regulations, namely the principle of “Lex Superior Derogat Legi Inferiori”. The Regent Regulation should guide or adjust to the updated Regional Regulations and display the old regulations. From these problems arise the question of factors causing disharmonization. This research is a field research data obtained through interviews with the legal bureau section of the Tanah Datar Regent office then the data is narrated descriptively. Results are discussed with the theories put forward. This study found that it has violated the rules of blinding laws and regulations, namely the hierarchy of legislation as explained in Law Number 15 of 2019 concerning the Establishment of Laws and Regulations.